Pharmacokinetics and bioequivalence of two formulations of the S-1 (tegafur/gimeracil/oxonate) capsule in Chinese cancer patients under fasting and fed conditions: a multicenter, randomized, open-label, single-dose, double-cycle crossover study - Lu, Junli; Lei, Yuyan; Mo, Yuanyuan; Wang, Xiangping; Liu, Wanying; Yan, Yu; Yang, Hongying; Li, Canxia; Huang, Lifeng; Shen, Qiuxia; Wang, Caihong; Chen, Jingjie; et al. (Frontiers in Pharmacology, 2025)
ObjectiveS-1, an oral multicomponent capsule containing tegafur, gimeracil, and potassium oxonate, has demonstrated efficacy in various tumor types. This study aimed to assess the pharmacokinetics, bioequivalence (BE), and safety of a newly developed generic S-1 capsule compared to the original brand-name formulation in Chinese cancer patients under fasting and fed conditions.MethodsA multicenter, randomized, open-label, single-dose, double-cycle crossover study was conducted in Chinese cancer patients. The study involved 120 subjects, with 60 assigned to the fasting group and another 60 to the fed group. In each study cycle, subjects were randomly assigned toreceive either the reference or test S-1 capsule at a 7-day interval. Blood samples were collected for analysis within 48 h after ingestion. The plasma concentrations of tegafur, 5-fluorouracil, gimeracil, and potassium oxonate were determined by liquid chromatography–tandem mass spectrometry (LC-MS/MS). The main pharmacokinetic (PK) parameters were calculated using the non-compartmental approach. BE was assessed through geometric mean ratios (GMRs) between the two formulations and their respective 90% confidence intervals (CIs). The safety of the two formulations was also evaluated.ResultsThe pharmacokinetics of the two formulations were similar under both fasting and fed conditions. The 90% CIs of the GMRs for the maximum observed serum concentration (Cmax), AUC0-t, and AUC0-∞ ratios were observed to lie within the BE acceptance range of 80%–125%. Both formulations of the S-1 capsule exhibited similar adverse events (AEs), primarily including decreased white blood cell count and hypertension. These AEs were generally mild and transient. The safety profiles of the two formulations were found to be good and comparable, with no serious adverse events (SAEs) reported.ConclusionThe newly developed generic S-1 and reference formulations exhibit comparable PK in Chinese cancer patients in the fasting and fed state. The formulations of S-1 showed good tolerability and a similar safety profile.Clinical Trial Registrationhttp://www.chinadrugtrials.org.cn/index.html, identifier CTR20171562.